Enhancing Emotion-Regulation Skills in Police Officers: Results of a Pilot Controlled Study - Berking, Matthias; Meier, Caroline; Wupperman, Peggilee (Behavior Therapy, 2010)
Police officers are routinely exposed to situations that elicit intense negative emotions; thus, officers have a particularly strong need for effective methods of regulating such emotions. The main purpose of this study was to investigate whether a manualized emotion-regulation training (Integrative Training of Emotional Competencies; iTEC; Berking, 2010a) can improve the emotion-regulation skills of police officers. First, self-reports of 9 emotion-regulation skills were assessed in a sample of officers (N=31) and compared to those of a matched community-based control group. Then, the effects of the training on the emotion-regulation skills of officers were evaluated in a time-staggered design with a waitlist control condition. Results indicate that, compared to controls, officers have difficulties in accepting and tolerating negative emotions, supporting themselves in distressing situations, and confronting emotionally challenging situations. The training significantly enhanced successful skill application, especially some skills with which officers reported difficulty applying. These findings suggest that a focus on emotion-regulation skills may be an important component for programs aimed at preventing mental-health problems in police officers. © 2010.
Created from Fastlane, Scopus look-up